Developing children's creativity and participation through a community development project - Muda, Suhaini; Hillaluddin, Azlin Hilma (Common Ground Research Networks, 2007)
This is a study of children's participation development which focused on Yellow House, a children's organisation in Klang Valley, Malaysia, established with a mission to develop children's creativity and participation. This organisation was established in conjunction with Article 31 of the Convention on the Rights of the Child (CRC) that stresses the right of the child to leisure, play and participation in cultural and artistic activities. The study investigated and analysed the activities and programmes organised by Yellow House, focusing on how children were given the opportunity to participate in the activities and programmes. This paper highlighted a proportion of the study that focused on activities carried out for children from residential cares and poor community areas in Klang Valley under the HE(althy)ARTS Programme from the year 2004 to 2005.